Cross-border Relations and Cooperation, the case of the Costa Rica-Panama dyad - Hernández Ulate, Aurora (2013)
This article refects on the cooperation between the border communities of the dyad Costa Rica - Panama, in order to group them thematically and represent them in a geography space.This study is based on economic,trade, environmental and social and institutional cross-border relations.The results show how localities in this dyad develop alliances and informal cooperation schemes that help themto face the challenges of local border development.